Faktor Penentu Kejadian Stunting pada Anak Balita di Wilayah Kerja Puskesmas Natarandang Kabupaten Ngada - Febby Magda Sulima; Anna Henny Talahatu; Marselinus Laga Nur (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
Stunting is a condition of growth failure in children under five where the length or height of the child is too short for their age due to chronic malnutrition. Malnutrition can occur since the baby is in the womb and only appears after two years of age. This study aims to analyze what factors influence the incidence of stunting in children under five years of age in the working area of Puskesmas Natarandang, Ngada Regency. This type of research is an analytic survey with a Case-Control Study research design. The sample size was 98 toddlers selected by proportional stratified reandom sampling. Data analysis used was univariate, bivariate and multivariate analysis with chi square test and multiple logistic regression. The results showed that the factors that influenced the incidence of stunting were the mother's education level (p=0.001), mother's occupation (p=0.000), family size (p=0.000), level of maternal nutritional knowledge (p=0.000), history of illness (p=0.002), feeding practices (p=0.000), health care practices (p=0.008) and environmental hygiene and santation practices (p=0.000), while the factor that did not affect the incidence of stunting was the family income level (p=1.000). The determinants of stunting were environmental hygiene and sanitation practices (OR=16.658) feeding practices (OR=9.217) and the level of maternal nutritional knowledge (OR=7.191). Stunting is a condition of growth failure in children under five where the length or height of the child is too short for their age due to chronic malnutrition. Malnutrition can occur since the baby is in the womb and only appears after two years of age. This study aims to analyze what factors influence the incidence of stunting in children under five years of age in the working area of Puskesmas Natarandang, Ngada Regency. This type of research is an analytic survey with a Case-Control Study research design. The sample size was 98 toddlers selected by proportional stratified reandom sampling. Data analysis used was univariate, bivariate and multivariate analysis with chi square test and multiple logistic regression. The results showed that the factors that influenced the incidence of stunting were the mother's education level (p=0.001), mother's occupation (p=0.000), family size (p=0.000), level of maternal nutritional knowledge (p=0.000), history of illness (p=0.002), feeding practices (p=0.000), health care practices (p=0.008) and environmental hygiene and santation practices (p=0.000), while the factor that did not affect the incidence of stunting was the family income level (p=1.000). The determinants of stunting were environmental hygiene and sanitation practices (OR=16.658) feeding practices (OR=9.217) and the level of maternal nutritional knowledge (OR=7.191).